Overweight and obesity: a remaining problem in women treated for severe gestational diabetes. Issue 8 (13th June 2016) - Hildén, K.; Hanson, U.; Persson, M.; Fadl, H.
Abstract: Aim: To analyse the impact of overweight and obesity on the risk of adverse maternal outcomes and fetal macrosomia in pregnancies of women treated for severe gestational diabetes. Methods: This was a population‐based cohort study including all singleton pregnancies in Sweden without pre‐existing diabetes in the period 1998–2012. Only mothers with an early‐ pregnancy BMI of ≥ 18.5 kg/m² were included. Logistic regression analysis was used to determine odds ratios with 95% CIs for maternal outcomes and fetal growth. Analyses were stratified by maternal gestational diabetes/non‐gestational diabetes to investigate the impact of overweight/obesity in each group. Results: Of 1 249 908 singleton births, 13 057 were diagnosed with gestational diabetes (1.0%). Overweight/obesity had the same impact on the risks of caesarean section and fetal macrosomia in pregnancies with and without gestational diabetes, but the impact of maternal BMI on the risk of preeclampsia was less pronounced in women with gestational diabetes. Normal‐weight women with gestational diabetes had an increased risk of caesarean section [odds ratio 1.26 (95% CI 1.16–1.37)], preeclampsia [odds ratio 2.03 (95% CI 1.71–2.41)] and large‐for‐gestational‐age infants [odds ratio 2.25 (95% CI 2.06–2.46)]. Risks were similar in the overweight group without gestational diabetes, caesarean section [odds ratio 1.34 (1.33–1.36)], preeclampsia odds ratio [1.76 (95% CI 1.72–1.81)], large‐for‐gestational‐age [odds ratio 1.76 (95% CI 1.74–1.79)]. Conclusions: Maternal overweight and obesity is associated with similar increments in risks of adverse maternal outcomes and delivery of large‐for‐gestational‐age infants in women with and without gestational diabetes. Obese women with gestational diabetes are defined as a high‐risk group. Normal‐weight women with gestational diabetes have similar risks of adverse outcomes to overweight women without gestational diabetes. What's new?: Maternal overweight and obesity is associated with similar increments in risks of adverse outcomes and delivery of large‐for‐gestational‐age infants in women with and without gestational diabetes. Overweight without gestational diabetes has a similar impact on the risk of maternal outcomes, such as preeclampsia, caesarean section and fetal macrosomia, as does gestational diabetes in women of normal weight. Obese women without gestational diabetes have higher rates of caesarean section, preeclampsia and macrosomia than normal‐weight women with gestational diabetes. Despite treatment, women with gestational diabetes still face excess risks of adverse pregnancy outcomes.